2009
DOI: 10.1590/s0100-29452009000100023
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de aceroleiras (Malphigia emarginata D.C.), utilizando marcadores moleculares RAPD e características morfoagronômicas

Abstract: RESUMO -O conhecimento da variabilidade genética e da relação entre diferentes acessos de aceroleira é importante para maximizar o uso dos recursos genéticos para futuros programas de melhoramento. O objetivo deste trabalho foi avaliar a divergência genética entre 48 acessos de aceroleira, por meio de marcadores moleculares RAPD e características morfoagronômicas. Foram utilizados 25 iniciadores, possibilitando obter 108 marcadores, sendo observadas 92 marcas polimórficas. Os marcadores obtidos foram analisado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 10 publications
9
8
0
1
Order By: Relevance
“…A large distribution of genotypes was observed in most groups, indicating wide diversity between the evaluated genotypes. This high variability could be explained by the tendency of allogamy of species which have not yet been domesticated (Oliveira et al, 2009). This was also observed in the research of Santana et al (2011), who found high variability between 17 umbu-cajazeira (Spondias sp) accessions, which is a species under domestication.…”
Section: Resultssupporting
confidence: 61%
“…A large distribution of genotypes was observed in most groups, indicating wide diversity between the evaluated genotypes. This high variability could be explained by the tendency of allogamy of species which have not yet been domesticated (Oliveira et al, 2009). This was also observed in the research of Santana et al (2011), who found high variability between 17 umbu-cajazeira (Spondias sp) accessions, which is a species under domestication.…”
Section: Resultssupporting
confidence: 61%
“…Accessions 3, 6, 8, and 24 stood out with regard to fruit mass and ratio and accessions 16 and 21 were superior with regard to fruit mass and vitamin C content (Table 1). These accessions have potential for use as clonal varieties and also in future crosses because they were superior in at least two of the most important agronomic characteristics or stood out in at least one of them (Oliveira et al, 2009). Moreover, the pulp yield of these nine accessions was greater than 74%, which is the determinant for industrial yield.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this expansion, the genetic variability that exists in commercial orchards of acerola, which is mostly the result of seed propagation, is associated with some disadvantages such as the segregation of plant and fruit characteristics, resulting in highly heterogeneous orchards in terms of quality and quantity. This hinders farming practices, in particular the farms' harvesting systems (Moura et al, 2007;Oliveira et al, 2009). The lack of established commercial varieties that ensure high fruit quality and yield reflects the need to genetically improve the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Group 1 (G1) practically allocated all individuals, indicating wide diversity, and was subdivided into five groups (G1-A, G1-B, G1-C, G1-D, G1-E). Larger groups, composed by more individuals, cluster the pairs that present smaller distances, since the group size is delimited by a mean distance between pairs of individuals (Oliveira et al, 2009), and although the cambuizeiro have the autogamy mechanism, the diversity found can be explained by the tendency to allogamy (Oliveira et al, 2007).…”
Section: /8mentioning
confidence: 99%